Do Institutions Matter More For Services ? - Amin, Mohammad (The World Bank, 2006)
Recent empirical research has focused on the role of institutions in overall economic performance. This paper examines the impact of institutions on the relative performance of the service sector. Through cross-country level and growth regressions it establishes the following stylized fact: countries with better institutions have relatively larger and more dynamic service sectors. It suggests that regulatory and contract enforcing institutions play a key role in the development of service sectors because these sectors enter into a more complex web of transactions with the rest of the economy and are more prone to market failure due to asymmetric information